CoSi2 on Si(100): LEED investigations of the c(2x2) and (2 root 2x root 2) phases and comparison to a bulk crystal CoSi2(100) surface - Starke, Ulrich; Weiss, Wolfgang; Rangelov, Georgi; Fauster, Thomas; Heinz, Klaus; et al. (Surface Science, 1996)
A CoSi2(100) film of 12 Angstrom thickness was grown on Si(100) and investigated by low-energy electron diffraction (LEED). Two surface phases of the film can be prepared depending on the annealing temperature. The c(2 X 2) phase appearing first (350 degrees C) was compared to the c(2 X 2) structure of a bulk CoSi2(100) sample. Diffraction spot intensities are very similar for bulk and film samples. By a quantitative LEED analysis both surfaces are found to be arranged in a CaF2 structure terminated by its silicon layer. Additional Si adatoms in fourfold hollow sites form the c(2 X 2) periodicity. The second phase (600 degrees C) has a (2 root 2 X root 2)-R45 degrees periodicity. Here, the film is cracked and mixed with patches of clean (2 X 1)-Si(100), thus making the LEED pattern similar to a c(4 X 4) structure.
Keywords: low-energy electron diffraction (LEED); surface structure; surface relaxation and reconstruction; low index single crystal surfaces; epitaxy; solid phase epitaxy; silicon; cobalt; silicides